1997
DOI: 10.1046/j.1365-2265.1997.1480961.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of nuclear DNA pattern and its relationship with cell cycle activity parameters in multinodular goitre

Abstract: The findings of increased proliferation rate in goitres with an aneuploid or neoplastic component suggests that some factors involved in goitrogenesis could also be responsible for the development of chromosomal aberrations and/or for the selection of cellular clones endowed with high growth potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…We have also observed aneuploidy in 18.5% of cases of nodular goiter, a percentage which is in accordance with the previously reported range of 10-22% [13,18,30,37]. Most of the aneuploid nodules in the present series displayed either papillary hyperplasia or foci of fetal-embryonal growth pattern (data not shown) and may represent, according to some authors, true neoplasms rather than hyperplastic lesions [1].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We have also observed aneuploidy in 18.5% of cases of nodular goiter, a percentage which is in accordance with the previously reported range of 10-22% [13,18,30,37]. Most of the aneuploid nodules in the present series displayed either papillary hyperplasia or foci of fetal-embryonal growth pattern (data not shown) and may represent, according to some authors, true neoplasms rather than hyperplastic lesions [1].…”
Section: Discussionsupporting
confidence: 93%
“…In the benign lesions of the thyroid, the percentage of cases with abnormal DNA content varies from 10% to 22% in goiters [13,18,31,37] and from 18% to 52% in follicular adenomas [8,18,22,34]. The prevalence of abnormal DNA content is particularly high in Hürthle cell adenomas [6,7,40].…”
Section: Introductionmentioning
confidence: 99%
“…For many years aneuploidy was considered as a sign of malignancy, but several studies have demonstrated that chromosomal instability (CIN) can also occur in benign diseases such as angioimmunoblastic lymphadenopathy, monoclonal gamapathy 2 and ulcerative colitis 3 . In thyroid lesions, aneuploidy is rare in PTCs and is observed in about 57% of FTCs, in 10–25% of FTAs 4 and in 10–22% of multinodular hyperplasias 5–7 …”
Section: Introductionmentioning
confidence: 99%
“…Francis et al [45] explained the aneuploid nodular goitre cases by the possible development of chromosomal aberrations and/or the selection of cellular clones with high growth potential. Konarska et al [46] recorded the presence of nodular goitre cases with hypoploid DNA pattern; however they did not suggest an explanation.…”
Section: Galectin-3 X 400) 2-b: Follicular Carcinoma Showing Diffusementioning
confidence: 99%